The effect of cash flow on stock return of selected consumer product companies listed in bursa Malaysia / Nurzatul Ain Mohd Arip - Mohd Arip, Nurzatul Ain (2017)
This paper aims to find out the best indicator for stock return on Consumer Product in Malaysia listed in Bursa Malaysia. This study is to focus on stock return for Consumer Product companies in Malaysia. It is involving the relationship between independent variables and dependent variables such as Cash Flows from Operating Activities, Cash Flows from Financing Activities, Cash Flows and Investing Activities towards stock returns. This study involved the observations in which consist of 15 consumer product companies, each company starting from year 2006 to 2015. The methodology used in this study is Regression Model with panel data sourced from Data Stream and Annual report. The interactive software package E-view 8 would be used for testing and analyzing the data collected. This study is an attempt to investigate the relationship of the chosen variables towards influencing the stock return. A finding from previous research mostly states that Cash Flows from Operating Activities affect the stock return. The result of this research paper would provide an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.